The Effect Of Exercises Using Rubber Ropes To Develop The Distinctive Strength Of Speed And The Performance Of The Skill Of Sending From The Top In Volleyball - Al-Zubaidi, Ali Hameed Ali (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The study aimed to identify the effect of exercises using rubber ropes in developing the distinctive strength of speed of the muscles of the arms, among students of the second grade of primary sports, as well as identifying the impact of these exercises in improving the performance accuracy of the skill of transmitting from above, As the amount of training units (12 weeks) and the research sample of (20) students representing Raie Al-Islah school, the researcher employed the experimental strategy in the pre- and post-measurement procedure. The players were divided into two groups of equal number, the first group experimental and the second group control, The results of the study revealed that rubber rope exercises have an effective impact on the development of (strength characteristic speed arms), and the researcher utilized the statistical bag to know the results of the search (SPSS), and helped to increase the skill of the transmitter from the top down. The researcher advised that physical and skill variables should be paid attention to in order to raise the level of performance of players. The study also advised that the remaining Najaf schools be informed of the study's findings in order to improve the physical and skill responses of volleyball players.